Bentuk Pertunjukan Wayang Kulit Bali Lakon Bhima Swarga dalam Upacara Pitra Yadnya - I Wayan Sugita; I Gede Tilem Pastika (Kamaya: Jurnal Ilmu Agama, 2022)
The Balinese shadow puppet show has a connection between the story that is told and the context of the yadnya ceremony. Mahabharata is an epic that is always the source of stories in Balinese shadow puppet shows, the storylines are often improvised by the puppeteers in the performances. Kawi dalang makes the story used more connected to the context of the implementation of the yadnya ceremony. One of the carangan stories that are often performed is the story of Bhima Swarga at the Pitra Yadnya ceremony. However, in the performance, the audience did not see this meaningful and unique performance. Therefore, it is necessary to conduct a study to find out the form of the performance, so that the reader knows the aspects of the form in the Balinese shadow puppet show Bhima Swarga story. The method used in this research is descriptive qualitative. The results of this study are in the form of a description and analysis of the synopsis, the structure of the performance, the form of the puppet characterizations, the language and vocals used, the musical accompaniment, the offerings used, and the stage set in the Balinese shadow puppet show Bhima Swarga story. all aspects of the form are integrated into a show that elevates Bhima as the central character and the story that is told can be used as an example in life to serve the ancestors.